Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models. Issue 29 (11th August 2016) - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja
Abstract : The guanidine–quinoline ligand dimethylethyleneguanidinoquinoline (DMEGqu) is able to stabilise bis(chelate) copper complexes in an intermediate geometry between tetrahedral and square‐planar environments. The structures of the obtained complexes model the entatic state and have been investigated in solid state by single‐crystal X‐ray diffraction and in the solid state and in solution by X‐ray absorption spectroscopy. The dimethylethyleneguanidine (DMEG) unit of the DMEGqu ligand displays a smaller steric encumbrance than the tetramethylguanidine (TMG) counterpart; this allows slightly larger structural changes upon oxidation than those for the TMG counterparts. Moreover, triflate coordination was possible for the Cu II DMEG complexes. DFT analyses revealed that good structural and optical descriptions are possible through the use of the hybrid functionals B3LYP and TPSSh in combination with the triple‐zeta basis set def2‐TZVP and the inclusion of empirical dispersion with Becke–Johnson damping and a suitable solvent model. The orbital analysis gives insights into the electronic structure of the complexes and their charge‐transfer behaviour. Abstract : A series of guanidine–quinoline copper complexes reveals that subtle influences such as the change in guanidine substitution have a large impact on the coordination distortion between tetrahedral and square‐planar environments and the role of these complexes as entatic‐state models.